Problem-Based Learning in Geography Education: The Effect on Spatial Thinking and Flood Preparedness Attitudes in Senior High School Student - Mike Mike; Syamsul Bachri; Heni Masruroh; Muhammad Aliman; Bayu Wijayanto; Bigharta Bekti Susetyo; Diky Al Khalidy (JAMBURA GEO EDUCATION JOURNAL, 2026)
Floods are a dominant hydrometeorological disaster in Indonesia, requiring early preparedness from the students. However, observations  show a gap between the high risk of flooding in the students' environment and their low spatial thinking skills and preparedness attitudes due to the dominance of conventional learning. This study aims to examine the effect of the Problem-Based Learning (PBL) model based on contextual problems on students' spatial thinking skills and preparedness attitudes towards flood disasters. This study used a quasi-experimental nonequivalent control group design, with two classes as research subjects, namely the experimental class and the control class. The data collection instruments used were a validated spatial thinking ability test and preparedness attitude questionnaire. Data analysis used the Independent Sample T-Test and Mann- Whitney U tests. The results showed that the PBL model had a significant effect on spatial thinking ability (p 0.001), with a large effect category (d = 1.045). In addition, PBL also had a significant effect on disaster preparedness attitudes (0 = 0.026), with a medium effect size (r = 0.306), as indicated by a change in category from "ready" to "very ready." This study proves that the integration of contextual flood problems in PBL syntax effectively stimulates students' spatial visualization and facilitates the internalization of risks that shape disaster response character. This study contributes to the development of geography learning strategies on disaster preparedness attitudes and emphasizes their application for a young generation that is resilient in facing hydrometeorological disasters